Final answer:
To solve for the red variable C in the equation R - C = P, subtract P from both sides and rearrange the equation to make C the subject.
Step-by-step explanation:
The equation you provided is R - C = P.
To solve for the variable C, we need to isolate it on one side of the equation. We can do this by subtracting P from both sides:
R - C - P = 0
Next, we can rearrange the equation to make C the subject:
-C = -R + P
Finally, to solve for C, we can multiply both sides by -1:
C = R - P
So the value of the red variable C is equal to R minus P.